Characterization of the key antigenic components of pertussis vaccine based on outer membrane vesicles - Ormazabal, Maximiliano Emanuel (2014)
Pertussis has resurged during the last two decades in different countries. In particular in the 2010–2013 period large outbreaks were detected in US, Australia, UK and The Netherlands with significant mortality in infants. The epidemiological situation of pertussis points out the need to develop new vaccines and in this regard we previously developed a new vaccine based on outer membrane vesicles (OMVs) which have been shown to be safe and to induce protection in mice. Here we have further investigated the properties of OMVs vaccines; in particular we studied the contribution of pertussis toxin (PTx) and pertactin (Prn) in OMVs-mediated protection against pertussis. PTx-deficient OMVs and Prn-deficient OMVs were obtained from defective Bordetella pertussis mutants. The absence of PTx or Prn did compromise the protective capacity of the OMVs formulated as Tdap vaccine. Whereas the protective efficacy of the PTx-deficient OMVs in mice was comparable to Prn-deficient OMVs, the protective capacity of both of them was significantly impaired when it was compared with the wild type OMVs. Interestingly, using OMVs obtained from a B. pertussis strain which does not express any of the virulence factors but expresses the avirulent phenotype; we observed that the protective ability of such OMVs was lower than that of OMVs obtained from virulent B. pertussis phase. However, it was surprising that although the protective capacity of avirulent OMVs was lower, they were still protective in the used mice model. These results allow us to hypothesize that OMVs from avirulent phase shares protective components with all OMVs assayed. Using an immune proteomic strategy we identified some common components that could play an important role in protection against pertussis.